Molecular hydrogen may enhance the production of testosterone hormone in male infertility through hormone signal modulation and redox balance. (December 2018) - Begum, Rahima; Bajgai, Johny; Fadriquela, Ailyn; Kim, Cheol-Su; Kim, Soo-Ki; Lee, Kyu-Jae
Abstract: Since the discovery of molecular hydrogen (H2 ) as a selective scavenger of free radicals like reactive oxygen species (ROS) and reactive nitrogen species (RNS), numerous studies have proved the potential application of H2 in therapeutic and preventative medicine. Moreover, H2 can regulate the intracellular signal as a signal modulator. However, it is still unclear in cell signaling involved in testosterone hormone production. Male fertility depends on the intra-testicular testosterone concentration, which is produced by the Leydig cell in the seminiferous tubules in testes. Although moderate amounts of ROS are needed for normal sperm function, the higher amounts might decrease testosterone production. High ROS decreases testosterone hormone production by dysregulation of hormonal signal from the hypothalamus to the Leydig cell as a result of redox imbalance. Lower level of testosterone fails to support the Leydig cell for the progression of spermatogenesis. Superoxide anion (O2 − ), hydroxyl radical ( OH) and peroxynitrite (ONOO − ) could also attack the DNA, lipid and protein, disrupting sperm structure and function and aggravating the milieu of male fertility and spermatogenesis. H2 regulates intracellular MAPK downstream cAMP signal and Ca 2+ signal as a signal modulator to antagonize ROS signaling. Thus H2 can play a role in modulating signals involved in testosterone hormone production to improve male fertility caused by redox imbalance. We therefore hypothesize that molecular hydrogen may enhance testosterone production via cellular redox balance. By this hypothesis, we anticipate that molecular hydrogen may be an effective remedy in male infertility.